Translocal feeds of faith: how mobility and digitalisation shape the religious life of young believers - Mattes-Zippenfenig, Astrid (Journal of contemporary religion, 2025)
Our increasingly digital and mobile world allows us to stay connected to people, places, and communities all over the world. This affects the religious lives of young believers who utilise the possibilities of mobility and digitalisation. So far, research on (digital) religion and migration has failed to assess translocal ties as decisive factors of youth religiosity. This omission is particularly problematic since the Covid-19 pandemic has increased the importance of digital communication and accelerated religious transformation processes. To understand the mutual effects of digitalisation and mobility on contemporary religion better, we enquire how digitally maintained translocal ties shape the religious lives of young believers. In a qualitative study involving young people of different religious traditions living in Vienna, we conducted interviews that included a mapping activity and a ‘social media tour’. Our findings illustrate how young believers establish translocal connections as reference points for their rather individualised personal faith and maintain ties through social media. This produces ‘translocal feeds of faith’ that represent, refresh, and advance the experiences that were made offline, complemented by purely digital ties emerging from personal interests. We find that translocal feeds of faith are an important starting point for studying lived religion among young believers.